E-System Perpajakan pada Kepatuhan Wajib Pajak Dimediasi oleh Variabel Locus of Control - Yudha, Cok Krisna; Putra, I Made Wianto (E-Jurnal Akuntansi, 2023)
This study aims to determine the impact of electronic systems on taxpayer compliance with orbit control as a parameter. The research sample collection method uses a non-probabilistic sampling method, namely random sampling. The data collection method is distributing questionnaires to 100 taxpayers. The Partial Last Square (PLS) model is the technique used in this study. The results showed that the E-system had a positive and significant effect on Locus of Control, Locus of Control had a positive and significant effect on taxpayer compliance, the E-system had a positive and significant effect on taxpayer compliance. Research also shows that the Locus of Control is able to mediate the influence of the E-system on taxpayer compliance. Keywords: Taxation E-System; Taxpayer Compliance; Locus of Control